(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The human Rights, a subject of animated discussion at regional and global today are often called Fundamental Rights or Natural Rights or the Rights of Man. The Term Human Rights refer in general the Civil Rights, Civil liberties, the Political rights and newly emerging social and economic rights.